Thoughts on a Multidimensional Middle School Index of College Readiness. Issue 3 (13th September 2016) - Mattern, Krista; Allen, Jeff; Camara, Wayne
Abstract : The findings of the Gaertner and McClarty article (2015) raised awareness on two extremely important topics related to college readiness: First, to effect change, we must measure students' progression towards college readiness throughout their K‐12 career rather than just at the culmination of high school. Second, college readiness encompasses more than academic preparation, and indices can be designed to weight additional factors according to their prediction of readiness. The reply by Lazowski, Barron, Kosovich, and Hulleman (this issue) added to the conversation by raising important issues around the measurement of motivation. In this reply, we provide our own thoughts on college and career readiness and offer ideas for additional work to further the development of college and career readiness indices.